2017
DOI: 10.1016/j.ijpe.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Robust and resilient strategies for managing supply disruptions in an agribusiness supply chain

Abstract: Agribusiness supply chains involve more sources of uncertainty than typical manufacturing supply chains due to attributes such as long supply lead-times, seasonality, and perishability. Therefore, it is critical but challenging to mitigate risks in agribusiness supply chains. However, the extant literature includes limited quantitative research on robust and resilient strategies for agribusiness supply chain risk management, particularly when perishability is explicitly modeled. In this paper, we investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 38 publications
(50 reference statements)
0
74
0
14
Order By: Relevance
“…This study argues that it is possible for a firm to possess both components of operational resilience and that each component plays unique and important role in disruption management (Li et al, 2019;Behzadi et al, 2017;Brandon-Jones et al, 2014). In line with the disruption profile framework, we contend that it may be difficult for a firm to activate both components of operational resilience simultaneously in that disruption absorption would logically and practically precede disruption recovery actions.…”
Section: Conceptualization Of Operational Resiliencementioning
confidence: 60%
See 2 more Smart Citations
“…This study argues that it is possible for a firm to possess both components of operational resilience and that each component plays unique and important role in disruption management (Li et al, 2019;Behzadi et al, 2017;Brandon-Jones et al, 2014). In line with the disruption profile framework, we contend that it may be difficult for a firm to activate both components of operational resilience simultaneously in that disruption absorption would logically and practically precede disruption recovery actions.…”
Section: Conceptualization Of Operational Resiliencementioning
confidence: 60%
“…In essence, possession of disruption absorption does not prevent a firm from possessing recoverability, and vice versa. Additionally, the fact that a firm has disruption absorption does not necessarily imply that the firm has recoverability (Behzadi et al, 2017). As Holling (1973) asserts, a system can be 'resilient' (i.e., persist in the face of disruptions) and yet lack 'stability' (i.e.…”
Section: Conceptualization Of Operational Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Chen, Zhang, and Delaurentis (2014) developed a model to study the 'quality measures' in FSC via a case study and concluded that the decentralized SC lead to distortion in food quality. Behzadi, O'Sullivan, Olsen, Scrimgeour, and Zhang (2017) investigated the effectiveness of robust and resilient strategies along with the profit gain through optimal RM and SC planning decisions. Mangla, Sharma, and Patil (2016) proposed that it is expected to focus on basic success factors to enhance the execution of FSCM practices.…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…Therefore, the major task of supply chain management is accurate and timely collection of customers' demand and delivering a right product with the right quality at the right time and the right location [1]. One of the most challenging problems in supply chain management is the conflicts that may occur between supply chain entities or inside each of them [2,3].…”
Section: Introductionmentioning
confidence: 99%